Biogeography and ecology of the upper montane rain forest of Sri Lanka (Ceylon) - Werner, Wolfgang L. (Tropical montane cloud forests, 1995)
Tropical evergreen rain forest forms the natural vegetation of the mountains of Sri Lanka. Lower montane rain forest covers the slopes between 900 and 1,500 m asl. The 1,500-m line is a sharp boundary between lower and upper montane rain forest, as it is the lower limit of a frequent and dense cloud cover.
Gesehen am 29.06.2021